Isolation of high molecular weight and humic acid-free metagenomic DNA from lignocellulose-rich samples compatible for direct fosmid cloning - Sar, Abhijit; Pal, Srikanta; Dam, Bomba (Applied microbiology and biotechnology, 2018)
Activity-based screening of metagenomic DNA libraries is a promising approach to fish out genes encoding novel bioactive compounds/enzymes of industrial importance. The starting point of such functional screening in fosmid vectors is isolation of high molecular weight (HMW) DNA of sufficient purity from diverse environments. Metagenomic DNA isolation protocols mostly employ mechanical cell lysis that yields fragmented DNA. Those established for HMW DNA using enzymatic lysis have not considered samples with high lignocellulose or humic acid content. Enzymes from such environments are in great demand for bioenergy, paper, and related industries. Thus, an improved method was standardized that has three key features, i.e., use of harvested microbial biomass instead of raw samples, removal of humic substances prior to cell lysis by aluminum sulfate flocculation, and enzymatic/chemical lysis of cells with a lysozyme, mutanolysin, proteinase K, and SDS cocktail followed by phenol-chloroform extraction and precipitation of DNA by polyethylene glycol and NaCl. HMW DNA (~ 40 kb) was efficiently isolated from garden and forest soils, rice straw compost, and degrading wood from a hypersaline lake. The humic acid removal efficiency across samples was 96–98%. The isolated DNA was of high quality/purity and could be successfully used in downstream applications like PCR, ligation, and fosmid cloning. In fact, the DNA was directly used without any size selection, for fosmid library preparation with 70–90% efficiency as compared to the control insert. Thus, the method could suitably be used for HMW DNA isolation for the functional screening of enzymes from diverse humic acid-/lignocellulose-rich environments.